2016
DOI: 10.1136/oemed-2016-103550
|View full text |Cite
|
Sign up to set email alerts
|

Can psychosocial work conditions protect against age-related cognitive decline? Results from a systematic review

Abstract: According to the use it or lose it hypothesis, intellectually stimulating activities postpone age-related cognitive decline. A previous systematic review concluded that a high level of mental work demands and job control protected against cognitive decline. However, it did not distinguish between outcomes that were measured as cognitive function at one point in time or as cognitive decline. Our study aimed to systematically review which psychosocial working conditions were prospectively associated with high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 42 publications
5
48
0
1
Order By: Relevance
“…This could imply that social interactions do explain whatever association might exist between community group engagement and dementia risk. Another possible explanation for why we did not see such strong results for community group engagement is that there can be an overlap with activities not carried out for leisure but rather for work, which could lead to feelings of stress or burden 35. Indeed, our index included attendance at socially responsible groups such as political groups, tenant’s associations and neighbourhood watch groups alongside more pleasure-oriented groups.…”
Section: Discussionmentioning
confidence: 92%
“…This could imply that social interactions do explain whatever association might exist between community group engagement and dementia risk. Another possible explanation for why we did not see such strong results for community group engagement is that there can be an overlap with activities not carried out for leisure but rather for work, which could lead to feelings of stress or burden 35. Indeed, our index included attendance at socially responsible groups such as political groups, tenant’s associations and neighbourhood watch groups alongside more pleasure-oriented groups.…”
Section: Discussionmentioning
confidence: 92%
“…Studies has indicated that intellectually challenging activities and active interpersonal exchanges can increase or maintain cognitive reserve, allowing individuals to cope longer before cognitive impairment is manifested [ 42 ], and produce beneficial effects on cognition even in old age [ 13 ]. Studies of cognitive reserve suggest that there are individual differences in the ability to cope with the brain pathologic changes [ 43 , 44 ] and cognitive reserve may be improved by exposure to an enriched environment such as social interaction or mentally challenging activity, physical activity, education [ 45 ], and may buffer against age-related CD [ 46 ]. Biological mechanisms related to the vascular hypothesis could also partially explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies have tentatively related psychosocial working conditions to late-life cognition and dementia risk (62,63), but the evidence is still limited. To date, low job control, by itself or in combination with either high or low job demands (i.e., high job strain or passive job), has been linked to worse cognitive function (64)(65)(66)(67).…”
Section: Psychosocial Working Conditions Cognitive Decline and Demementioning
confidence: 99%